Super bounding surface development in a fluvial-aeolian interaction system: towards a model for food-generated "Stokes' surfaces" - Veiga, Gonzalo Diego (2017)
Super bounding surfaces are key elements for understanding the long-term evolution of aeolian systems and represent major changes in aeolian sediment budget triggered by extra-erg factors. Multiple paralleltruncation bedding planes (aka Stokes’ surfaces) have been widely described for ancient aeolian systems, associated with changes in the sediment budget and deflation to water table; although deflationis not a requisite and non-climbing, migrating ergs can also develop parallel-truncation planes. Deflationary or non-climbing conditions have been usually related to sustained dry conditions and exhaustion of the original sand supply. However, episodes of fluvial flooding may have major impact in the sedimentary budget of fluvially-sourced aeolian systems by increasing the amount of coarse-grained supply and/or rising the water table.